PERKEMBANGAN SUB SEKTOR PERKEBUNAN DAN KONTRIBUSINYA TERHADAP PRODUK DOMESTIK BRUTO JAWA TIMUR 1983-2001 - Imam Hidayat, Syarif (MAPETA, 2002)
The purpose of study is to analyze development of production and land area estate, Gross Regional Domestic Product than what share estate to GRDPat East Java (1983-2001) so what good alternative strategies based on the present secondary data. The increation of production, land area, GRDP and share commodities estate to GRDP using trend model.Therefore to terminate strategy by SWOTanalysis. In 1983-1992 appear the positive increasing in production, land area and GORP so share estate at East Java. But in 1993-2001 so low periodic. One of reasoning is monetery crisis beginning about 1997, July. To win competition suggested to create new market,a good product with minimized weaknesses and the optimal opportunities. Keywords: Estate, Contribution,Gross RegionalDomesticProduct